Pengaruh kurs, net ekspor, dan penanaman modal asing terhadap pertumbuhan ekonomi Indonesia - Tuty Cahya Azizah; Haryadi Haryadi; Etik Umiyati (e-Journal Perdagangan Industri dan Moneter, 2019)
The purpose of this study is to analyze the development of exchange rates, net exports, FDI, and Indonesia's economic growth in 1998-2017 and to analyze the effect of exchange rates, net exports, and foreign investment (FDI) on Indonesia's economic growth in 1998-2017. used in this study is secondary data sourced from the Central Statistics Agency (BPS). The analytical tool used in this study is descriptive and quantitative analysis, namely by multiple linear regression. The research method used in this study is the "Ordinary Least Square (Ordinary Least Square) method. OLS). The test results using OLS show that together the variables of the exchange rate, net exports, and FDI have a significant effect on Indonesia's economic growth. While partially, the exchange rate has a positive and significant effect on Indonesia's economic growth. Meanwhile, net exports have a positive and significant impact on Indonesia's economic growth. Meanwhile, FDI has a positive and significant impact on Indonesia's economic growth. Keywords: Exchange rate, Net exports, Foreign investment, Economic growth.